Nonimmune immunoglobulin binding and multiple adhesion characterize Plasmodium falciparum-infected erythrocytes of placental origin - Rasti, Niloofar; Namusoke, Fatuma; Cheˆne, Arnaud; Chen, Qijun; Staalsoe, Trine; Klinkert, Mo-Quen; Mirembe, Florence; Kironde, Fred; Wahlgren, Mats (National Academy of Sciences, 2006)
The harmful effects of pregnancy-associated malaria (PAM) are engendered by the heavy sequestration of Plasmodium falciparum parasitized RBCs in the placenta. It is well documented that this process is mediated by interactions of parasite-encoded variant surface antigens and placental receptors. A P. falciparum erythrocyte membrane protein 1 variant, VAR2CSA, and the placental receptor chondroitin sulfate A (CSA) are currently the focus of PAM research. A role for immunoglobulins (IgG and IgM) from normal human serum and hyaluronic acid as additional receptors in placental sequestration have also been suggested. We show here (i) that CSA and nonimmune IgG IgM binding are linked phenotypes of in vitro-adapted parasites, (ii) that a VAR2CSA variant shown to bind CSA also harbors IgG- and IgM-binding domains (DBL2-X, DBL5- , and DBL6- ), and (iii) that IgG and IgM binding and adhesion to multiple receptors (IgG IgM HA CSA) rather than the exclusive binding to CSA is a characteristic of fresh Ugandan placental isolates. These findings are of importance for the understanding of the pathogenesis of placental malaria and have implications for the ongoing efforts to develop a global PAM vaccine.
Keywords: Nonimmune immunoglobulin; Adhesion; Plasmodium falciparum-infected erythrocytes; Placental origin